2016
DOI: 10.7554/elife.13926
|View full text |Cite
|
Sign up to set email alerts
|

Activation of individual L1 retrotransposon instances is restricted to cell-type dependent permissive loci

Abstract: LINE-1 (L1) retrotransposons represent approximately one sixth of the human genome, but only the human-specific L1HS-Ta subfamily acts as an endogenous mutagen in modern humans, reshaping both somatic and germline genomes. Due to their high levels of sequence identity and the existence of many polymorphic insertions absent from the reference genome, the transcriptional activation of individual genomic L1HS-Ta copies remains poorly understood. Here we comprehensively mapped fixed and polymorphic L1HS-Ta copies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
194
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(220 citation statements)
references
References 101 publications
21
194
2
Order By: Relevance
“…Among these, one insertion originated from a donor L1 on Chromosome 22 previously found to be responsible for tumor-specific L1 insertions in other human cancer types (Pitkanen et al 2014;Tubio et al 2014;Paterson et al 2015). An increasing body of evidence suggests that a particular subset of retrotransposition-competent L1 loci tend to be recurrent contributors to genomic instability in human malignancies and cancer cell lines (Tubio et al 2014;Philippe et al 2016;Scott et al 2016;Gardner et al 2017). Indeed, here we found that the promoter region of the TTC28 donor L1 was largely demethylated in both nontumor liver and matched ICC tumor cells, as a prior study found for a Chromosome 17 donor L1 responsible for APC exon mutagenesis in a colorectal cancer patient (Scott et al 2016).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Among these, one insertion originated from a donor L1 on Chromosome 22 previously found to be responsible for tumor-specific L1 insertions in other human cancer types (Pitkanen et al 2014;Tubio et al 2014;Paterson et al 2015). An increasing body of evidence suggests that a particular subset of retrotransposition-competent L1 loci tend to be recurrent contributors to genomic instability in human malignancies and cancer cell lines (Tubio et al 2014;Philippe et al 2016;Scott et al 2016;Gardner et al 2017). Indeed, here we found that the promoter region of the TTC28 donor L1 was largely demethylated in both nontumor liver and matched ICC tumor cells, as a prior study found for a Chromosome 17 donor L1 responsible for APC exon mutagenesis in a colorectal cancer patient (Scott et al 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Analysis of the 3 ′ transduced sequence identified a donor L1 on Chromosome 22 and intronic to the gene TTC28. Recent studies of 3 ′ transduction-bearing L1 insertions in tumor samples pointed to this element as a highly active donor L1 in human tumor cells (Pitkanen et al 2014;Tubio et al 2014;Paterson et al 2015;Philippe et al 2016;Gardner et al 2017). We therefore performed targeted bisulfite sequencing of the complete donor L1 promoter region, which was significantly demethylated in patient ICC.75 tumor compared to matched nontumor liver (P < 0.0001, paired t-test, two tailed) (Fig.…”
Section: A D C Bmentioning
confidence: 98%
“…Susceptibility to LINE-1 hypomethylation appears to be cell and tissue specific and might be dependent on cancer type or subsets of a specific cancer type 53–55 . Moreover, emerging evidence suggest that not all LINE-1s are regulated in the same way 56 . Global LINE-1 methylation studies are unable to provide evidence for a relationship between methylation at individual LINE-1 and their activity.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis involves integrating a combination of data types, including a genomic LINE-1 insertion map, RNA-seq reads, and chromatin immunoprecipitation (ChIP)-seq data (65). Actively transcribed LINE-1 loci have a two-part ‘signature’ : (i.)…”
Section: Introductionmentioning
confidence: 99%